Biodiversity assessment and sustainability communication in regional value chains of SMEs in the food sector - Zaremba-Warnke, Sabina; Seidel, Boris (Ocena bioróżnorodności i komunikowanie zrównoważoności w regionalnych łańcuchach wartości MŚP w sektorze spożywczym, 2019)
The aim of this paper is to assess the set of indicators developed by the authors within the framework of the project “Regional value chains in the context of biodiversity and ecosystem services − based on the example of Czech-Polish-Saxon research project collaboration”. The indicators can be used as a tool for evaluating the biodiversity performance of small and medium-sized food enterprises on a micro scale and for sustainability communicating in their value chains. After a short introduction and a literature review, the indicator set for agricultural businesses is presented. Based on qualitative surveys on selected farmers, this set was evaluated with the help of SWOT analysis elements. The survey results showed the weaknesses and strengths of the construction of the indicator set and also the opportunities and threats of its usage. Finally, recommendations for further research are presented, mostly connected with sustainability communication in regional value chains in food SMEs
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 258-270
Keywords: biodiversity assessment and management; regionalism; sustainability communication; ragional value chains; ocena i zarządzanie bioróżnorodnością; regionalność; komunikowanie zrównoważoności; regionalne łańcuchy wartości